Nonverbal Executive Function is Mediated by Language: A Study of Deaf and Hearing Children. Issue 5 (10th November 2016) - Botting, Nicola; Jones, Anna; Marshall, Chloe; Denmark, Tanya; Atkinson, Joanna; Morgan, Gary
Abstract : Studies have suggested that language and executive function (EF) are strongly associated. Indeed, the two are difficult to separate, and it is particularly difficult to determine whether one skill is more dependent on the other. Deafness provides a unique opportunity to disentangle these skills because in this case, language difficulties have a sensory not cognitive basis. In this study, deaf ( n = 108) and hearing ( n = 125) children (age 8 years) were assessed on language and a wide range of nonverbal EF tasks. Deaf children performed significantly less well on EF tasks, even controlling for nonverbal intelligence and speed of processing. Language mediated EF skill, but the reverse pattern was not evident. Findings suggest that language is key to EF performance rather than vice versa.